INTER-OBSERVER AGREEMENT IN MRI ASSESSMENT OF LUMBER INTERVERTEBRAL DISCS AND NERVE ROOTS USING PFIRRMAN CLASSIFICATION - Saeed, Shahla Mohammed; Abass, Abeer Kadum; Rasool, Mariwan Mahmood (Journal of Sulaimani Medical College, 2019)
Background Low back pain is a common medical condition and is a major health and economic problem. Intervertebral disc degeneration grading is crucial in the evaluation of many degenerative spine conditions including low back pain.MRI is considered the best imaging technique to evaluate intervertebral disc degenerative changes. Back pain is the most common indication for imaging of the spine. A morphologic Pfirrman grading system is commonly used to classify spinal degenerative changes ( intervertebral discs & nerve roots). Objectives The aim of this study was to evaluate the degree of independent interobserver agreement using Pfirrman classification in the assessment of disc degenerations and nerve root compromise. Patients and Methods This study was conducted in Sulaimani, Kurdistan Region, Iraq at the diagnostic imaging center in Sulaimania during the period of 21st April 2015 to 21st October 2015 for 50 patients with low back pain. The same images were interpreted by two radiologists independently for grades of disc degeneration and nerve root compromise using Ppfirrmann classification system, up to the authors' knowledge this is the first study in the Kurdistan Region that depends on interobserver agreement regarding MRI interpretations concerning degenerative lumbar spine changes. Results The interobserver agreement in our study for Pfirrman grades of disc degeneration and nerve root compromise was moderate with Kappa values of (K= 0.431) and (K=0.417) respectively. Conclusion Pfirrman classification system is reliable and provides a standardized assessment of lumbar intervertebral disc and nerve roots.
Keywords: Disc degeneration; Lumber MRI; Back pain